The effect of CPP-ACP and Nd:YAG laser on the bond strength of softened dentin - Maria Beatriz Beber KAMOZAKI; Anuradha PRAKKI; Letícia Carvalho Coutinho Costa PEROTE; Natalia Cortez GUTIERREZ; Clovis PAGANI (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The purpose of this study was to investigate the effect of CPP-ACP treatment and Nd:YAG laser on microtensile bond strength (µTBS) of softened dentin. Sixty samples were obtained from thirty sound third molars. All samples were submitted to dentin softening procedure, by the immersion of the specimens in 30 mL of Sprite Zero for 30min. Afterwards, the samples were randomly divided according to the CPP-ACP treatment: CG-Control group; MP-treated with CPP-ACP paste (MI Paste); MPP-treated with CPP-ACP+900 ppm NaF paste (MI Paste Plus). Each group was further divided according to bonding procedure: NL-No laser; L-Laser irradiation after adhesive application and before polymerization. The laser parameters used were 1.4 W, 10 Hz, 140 mJ/pulse, with an optic fiber of 320 µm, generating energy of 174 J/cm2 per pulse. All samples were restored with Clearfil SE Bond/Filtek Z350 XT. After 24 h, the restored samples were cut into beams (± 1 mm2 adhesive interface area) and subjected to a µTBS test. Data were analyzed by two-way ANOVA test and Holm-Sidak post-hoc method (α = 0.05). The treatment with CPP-ACP pastes did not significantly affect softened dentin µTBS (p = 0.070). Statistic revealed significant reduction on µTBS values for CG/L, leading to the rejection of the second null hypothesis (p < 0.001). Both CPP-ACP based pastes did not affect µTBS of softened dentin for the adhesive system utilized. The Nd:YAG laser irradiation after application of adhesive system did affect µTBS values of softened dentin samples untreated with CPP-ACP based pastes.